A DFT Study on Estrone – TNT Interaction1. Issue 10 (2nd July 2013) - Türker, Lemi; Çelik Bayar, Çağlar
Abstract Trinitrotoluene, known as TNT, is a widely used powerful explosive. It is a poisonous material, which injures almost all cells, especially those of liver, bone marrow, and kidney. Estrone is a sex hormone having an electron rich aromatic (phenolic) ring that is capable of forming a π complex with molecules containing an electron deficient π system. This study has focused on investigating the tendency of the complex formation of TNT with estrone. It has been thought that the formation of estrone‐TNT π complex might take place in a human body exposed to acute or prolong period of this hazardous chemical and consequently estrone activities might be impaired. The complex formation reaction was investigated mainly using DFT method with B3LYP/6‐31G(d, p) basis set in gas phase. The existence of π interaction between estrone and TNT was demonstrated by computational spectroscopic analyses (UV/Vis, IR, and 1H NMR techniques). The frontier molecular orbital (HOMO and LUMO) analyses have shown that the considered π complex is very resistant to oxidation with respect to its components, estrone and TNT.